Current advances in haploid stem cells - Cui, Tongtong; Li, Zhikun; Zhou, Qi; Li, Wei (Protein & cell, 2020)
Diploidy is the typical genomic mode in all mammals. Haploid stem cells are arti cial cell lines experimentally derived in vitroin the form of different types of stem cells, which combine the characteristics of haploidy with a broad developmental potential and open the possibil- ity to uncover biological mysteries at a genomic scale. To date, a multitude of haploid stem cell types from mouse, rat, monkey and humans have been derived, as more are in development. They have been applied in high-throughput genetic screens and mammalian assisted reproduction. Here, we review the generation, unique properties and broad applications of these remarkable cells.